ANALISIS PENGARUH PERSEPSI KUALITAS, KEAMANAN, DAN KEMANFAATAN PADA KEPUASAN DAN LOYALITAS KONSUMEN âTOLAK ANGINâ - , Normayola Classic., S.Farm ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the current time, the tendency and awareness of society in using traditional medicine has increased. Because of the increasing competition of traditional medicine market, the quality, safety, and efficacy are the main things which must be considered by any producers of traditional medicine in order to achieve customer satisfaction and loyalty. Tolak Angin is a traditional medicine produced by PT. Sido Muncul which have earned a certificate of Standardized Herbal Medicines from National Agency of Drug and Food Control of Indonesia. This study aims to analyze the influence of the perceived quality, safety, and efficacy of Tolak Angin on customer satisfaction and loyalty. This study used a survey method with the entire population of consumers Tolak Angin in Yogyakarta, meanwhile the sampling used purposive sampling method. The independent variables of first hypothesis (H 1), second (H 2 ), and third (H 3 ) are quality, safety, and efficacy and the dependent variable is satisfaction. While the hypothesis 4 (H 4 ), the satisfaction is an independent variable and loyalty as a dependent variable. All variables were measured using a Likert scale. Primary data were obtained using a questionnaire administered to 210 respondents. Validity test of the research instrument with Confirmatory Factor Analysis and reliability test with Cronbach's Alpha, whereas hypothesis testing using linear regression analysis. The results showed that the perceived quality, safety, and efficacy had significantly positive effect on customer satisfaction, and customer satisfaction had significantly positive effect on customer loyalty. The Influence of the perceived quality, safety, and efficacy on customer satisfaction was 60.40%. The efficacy gave the greatest influence on customer satisfaction (Î²=0.478), while safety gave the smallest influence on consumer satisfaction (Î²=0.136). The influence of customer satisfaction on customer loyalty was 42.80%.